DAY NIGHT VARIATION IN PHAGOCYTOSIS AND SUPEROXIDE PRODUCTION BY LEUCOCYTES IN FRESHWATER SNAKE, NATRIX PISCATOR - ALKA SINGH; RAMESH SINGH (The Bioscan, 2012)
Aim of the present study was to understand the diurnal variation in phagocytosis and superoxide production by blood leucocytes in the fresh water snake, Natrix piscator. Leucocyte phagocytosis and superoxide production are important constituents of innate immune response and form the first line of host defense. Yeast (Saccharomyces cerevisae) cells were used as target cell to study phagocytosis. Oxidative burst activity was measured by reduction of a tetrazolium dye. Snakes were sacrificed at mid day and mid night. Blood was obtained through cardiac puncture, and leucocytes were separated. Equal amount of blood and yeast cells were incubated for 30 minutes, and smear of mixture was prepared on a clean glass slide. Slides were stained and observed in oil immersion. Percent phagocytosis was significantly (p<0.05) higher (60.75±1.89) during mid day as compared to mid night (50.75±1.18). Phagocytic index showed non significant increase during mid night (2.44±0.20) when compared to mid day (2.21±0.25). Superoxide production was found to be significantly higher during night (0.357±0.02) as compared to day (0.255±0.02). It is suggested that diurnal variation is a part of immune system circadian oscillation.